Charles S. Pierce's Semiotic Study of the Last Days in QS. Al-Haqqah: Trichotomy Relations (Icons, Indexes and Symbols) - Zahrotun Zahrotun (Yayasan Insan Mulia Bima, 2024)
This research aims to examine the meaning of the Day of Judgment in Surah Al-Haqqah and analyze the vocabulary within it through Peirce’s semiotic study. According to Charles Sanders Peirce’s semiotics, signs based on their relationship with their objects are divided into three categories: icons, indexes, and symbols. Surah Al-Haqqah depicts a highly tense atmosphere and narrates the consequences for those who disobey in the world. It clearly illustrates human actions, both good and bad, as no creature can hide from His presence. This research employs a qualitative approach. The analysis reveals that out of the fifty-two verses in Surah Al-Haqqah, there are six quotations related to the Day of Judgment categorized as icons. Additionally, there are ten index quotations scattered throughout the surah. Finally, among the fifty-two verses, the most frequently found type of symbol is found in seventeen verses.